The Effects of a Fixed Combination of Berberis aristata and Silybum marianum on Dyslipidaemia – A Meta-analysis and Systematic Review - Tóth, Barbara; Németh, Dávid; Soós, Alexandra; Hegyi, Péter; Pham-Dobor, Gréta; Varga, Orsolya; Varga, Viktória; Kiss, Tivadar; Sarlós, Patrícia; Erőss, Bálint; Csupor, Dezső (Planta Medica, 2020)
A fixed combination of Berberis aristata and Silybum marianum (Berberol) has been used by patients with dyslipidaemia. The aim of the present meta-analysis was to systematically evaluate the efficacy and safety of a fixed combination of B. aristata and S. marianum (Berberol) on serum lipid levels compared to placebo in a meta-analysis based on randomised, controlled trials. The meta-analysis was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement, using the PICO (patients, intervention, comparison, outcome) format, and it was registered in the International Prospective Register of Systematic Reviews. The Cochrane Central Register of Controlled Trials, PubMed, Embase, and Web of Science databases were searched for relevant studies. Placebo-controlled clinical studies involving adult patients with a condition of dyslipidaemia and receiving a fixed combination of B. aristata and S. marianum were included. Four randomised trials, including a total of 491 patients, were pooled in statistical analysis. According to the present meta-analysis, Berberol significantly lowered the low-density lipoprotein level, total cholesterol, fasting plasma glucose levels, and the Homeostatic Model Assessment index compared to placebo; however, its effects on the high-density lipoprotein level, triglyceride level, and body mass index were not statistically significant by the end of a 3-month treatment period. Berberol appeared to be safe, and it did not increase the levels of alanine transaminase, aspartate transaminase, and creatine kinase enzymes. Berberol is an effective and presumably safe complementary therapy for the treatment of dyslipidaemia; however, the evidence supporting its use is very limited. The optimum dose and duration of treatment are unclear. A comprehensive evaluation of efficacy and safety is required in further high-quality clinical studies involving larger patient populations.
Keywords: silymarin; Silybum marianum; Compositae; berberine; Berberis aristata; Berberidaceae; dyslipidaemia; meta-analysis